PENERAPAN METODE DEMONSTRASI UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV PADA MATA PELAJARAN IPA DI SDN 92/VII PEMATANG KOLIM I - Fany Anggi Kustianingrum; Suprapno; Beni Husmansyah (STKIP Subang, 2025)
This study was motivated by the low learning outcomes of Grade IVA students in science subjects, particularly on the topic of changes in energy forms. Many students still had difficulty understanding concepts concretely because the learning process was predominantly teacher-centered and provided limited hands-on experience for students.This research employed Classroom Action Research (CAR), conducted in two cycles consisting of the stages of planning, implementation, observation, and reflection. In each cycle, the demonstration method was applied to improve students’ learning outcomes and learning activities. In Cycle I, the teacher demonstrated the science material while students observed and took notes; however, some students were still less active. In Cycle II, the method was improved by directly involving students in the demonstrations, resulting in a clear increase in student activeness and understanding. The results showed an improvement in the learning outcomes of Grade IVA students. In the initial condition, only 5 students (26.3%) achieved the Minimum Mastery Criteria (KKM). After the implementation of the demonstration method in Cycle I, the number of students who achieved mastery increased to 15 students (78.9%). In Cycle II, all students (19 students or 100%) successfully achieved scores above the KKM. Student learning activities also improved from the low category to the high category.